ANALISIS PERBEDAAN TINGKAT PENDAPATAN PEDAGANG SAYUR SESUDAH DAN SEBELUM RELOKASI DARI PASAR MERJOSARI KE PASAR LANDUNGSARI - Fadlan Fadlan; Zainal Arifin (Program Studi Ekonomi Pembangunan, 2017)
This research aimed to know the characteristics of vegetable traders who are relocated from Merjosari Market to Landungsari Market and to know the differences income levels after and before relocation. This research is descriptive quantitative and analyzed using different test (t test) by SPSS application. The results concluded that there is no difference of vegetable selling price, quantity of sales, total cost and significant business efficiency experienced by vegetable traders after and before relocation from Merjosari Market to Landungsari Market. So it does not make a significant difference in income. The income difference between after and before relocation is only Rp. 1.855.769. That is, every trader on average only increased revenue of Rp. 61.859.Keywords: Relocation, traders, income.